Clinical Characteristics and Reasons for Differences in Duration From Symptom Onset to Release From Quarantine Among Patients With COVID-19 in Liaocheng, China - Tian, Suochen; Chang, Zhenqin; Wang, Yunxia; Wu, Min; Zhang, Wenming; Zhou, Guijie; Zou, Xiuli; Tian, Hui; Xiao, Tingfang; Xing, Junmin; Chen, Juan; Han, Jian; et al. (Frontiers in Medicine, 2020)
Objective: This study aimed to identify more characteristics and features of coronavirus disease (COVID-19) by assessing the clinical courses among COVID-19 patients in a region outside Hubei province. Methods: We analyzed retrospective data regarding the clinical courses among 37 adult patients with COVID-19. According to the duration from symptom onset to release from quarantine, the patients were divided into the ≤20-day and >20-day groups, and the similarities and differences between them were compared. Results: Among the 37 patients, 5 had mild disease, 30 had moderate disease. All the patients were released from quarantine. The average duration from symptom onset to release from quarantine was 20.2±6.6 days. The average duration from symptom onset to hospitalization was 4.1±3.7 days. The average age was 44.3±1.67 years and 78.4% of cases were caused by exposure to a patient with confirmed disease or the workplace of a patient with confirmed disease. The main symptoms were cough (67.6%), fever (62.2%), shortness of breath (32.4%), fatigue (24.3%). The white blood cell count was decreased in 27.0% of patients, and the lymphocyte count was decreased in 62.2% of the patients. On admission, 86.5% of patients showed pneumonia on chest CT scans. In the >20-day group, the average age was 49.9±1.38 years and the average duration from symptom onset to hospitalization was 5.5±3.9 days. Compared with the ≤20-day group, these patients were older and the duration was longer (P<0.05). When the 37 patients were released from quarantine, the white blood cell count of 16.2% of the patients was <4.0×109/L, the lymphocyte count of 59.5% of the patients was <1.1×109/L, and the absolute counts of white blood cells and lymphocytes were 5.02±1.34×109/L and 1.03±0.34×109/L, respectively, compared with those recorded on admission (P>0.05). Conclusion: The majority of COVID-19 cases in the study area were mild and moderate, with good clinical outcomes. There were some special characteristics in the clinical process. The reasons for the duration from symptom onset to release from quarantine were complex. There was no significant change in the number of granulocytes at the time of release from quarantine compared to that at the time of admission.